Systemic medications used in treatment of common dermatological conditions: safety profile with respect to pregnancy, breast feeding and content in seminal fluid. (2nd January 2019) - Brown, Sarah Madeline; Aljefri, Khadija; Waas, Rachel; Hampton, Philip
Abstract: Prescribing for pregnant or lactating patients and male patients wishing to father children can be a difficult area for dermatologists. There is a lack of review articles of commonly used systemic medications in dermatology with respect to their effects on developing embryogenesis and their potential transfer across the placenta, in breast milk and in seminal fluid. This paper aims to provide an up to date summary of evidence to better equip dermatologists to inform patients about the effects of systemic medications commonly used in dermatology to treat conditions such as atopic dermatitis, psoriasis and acne, on current and future embryogenesis and fertility.